Perceiving the Demographic Profile and the Perception of the Chinese and Malays Visitors to Pulau Kukup National Park - Mohd. Yaman, Maheran; Nik Abdul Rahman, Nik Ismail Azlan (IIUM, 2010)
Pulau Kukup holds the distinction of being one of the largest protected mangrove island in the world. The 647hectare island is uninhabited and covered with mangroves. The mangrove forests here are one of the tallest tidal forests on the coast, with some trees reaching a height of 30m. The south-west side of the island consists of large areas of mudflats – an important food source for birds and other wildlife. A total of 12 species of vertebrate fauna and 23 species of birds – including the lesser adjutant stork – were recorded in the mangroves and mudflats. The wetland also supports such species as the Flying Fox Pteropus vampyrus, Smooth Otter Lutra perspicillata, Bearded Pig Sus barbatus, Long-tailed Macaque Macaca fascicularis, Pulau Kukup plays a vital role as one of the world’s most important wetland habitats; it is home to many rare and endangered species. The Johore government has declared Pulau Kukup a national park in 1985 and listed as a Ramsar site, a recognition that are deemed to have international importance and are included in the List of Wetlands of International Importance